2012
DOI: 10.1111/j.1747-0080.2012.01605.x
|View full text |Cite
|
Sign up to set email alerts
|

Identifying malnutrition risk in acute medical patients: Validity and utility of Malnutrition Universal Screening Tool and Modified Malnutrition Screening Tool

Abstract: Aim:  Nutrition screening is increasingly conducted in hospitals during the patient admission process. We aimed to explore the ease of use of two tools in the conduct of screening by nutrition technicians (NTs), and to compare validity. The tools are Malnutrition Universal Screening Tool (MUST) and Modified Malnutrition Screening Tool (Mod‐MST). Methods:  A sample of 262 consecutive adult hospital patients in medical wards was screened during December 2008 to January 2009. Trained NTs used both tools to screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…The study outlined in this paper aims to provide a new and detailed perspective on the burden, impact and diagnosis of PEM in a high income country setting and in an underserved population, in this instance, Indigenous Australians. The prevalence of PEM and those at-risk of malnutrition is significant in hospital inpatients (Allard et al 2015 ; Agarwal et al 2012 , 2013 ; Ultang et al 2012 ; Gibson et al 2012 ). PEM, in turn, has been associated with a number of adverse clinical outcomes (Allard et al 2015 ; Agarwal et al 2012 , 2013 ; Escott-Stump 2012 ; Lim et al 2012 ; Rowell and Jackson 2011 ; Saunder et al 2010 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study outlined in this paper aims to provide a new and detailed perspective on the burden, impact and diagnosis of PEM in a high income country setting and in an underserved population, in this instance, Indigenous Australians. The prevalence of PEM and those at-risk of malnutrition is significant in hospital inpatients (Allard et al 2015 ; Agarwal et al 2012 , 2013 ; Ultang et al 2012 ; Gibson et al 2012 ). PEM, in turn, has been associated with a number of adverse clinical outcomes (Allard et al 2015 ; Agarwal et al 2012 , 2013 ; Escott-Stump 2012 ; Lim et al 2012 ; Rowell and Jackson 2011 ; Saunder et al 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rates of hospital inpatient PEM vary greatly between surveys depending on the patient population and the methods used to diagnose malnutrition. In recent hospital-based surveys in Canada and Australia, using the Subjective Global Assessment (SGA), the prevalence of PEM in adult inpatients has been reported as ranging from 17 to 58 % (Allard et al 2015 ; Ultang et al 2012 ; Gibson et al 2012 ). Compared to well-nourished patients, surveys also demonstrated that malnourished patients had an increased length of hospital stay, higher rates of in-hospital mortality, more frequent hospital readmissions, and overall poorer longer-term survival rates (Allard et al 2015 ; Agarwal et al 2013 ; Lim et al 2012 ; Norman et al 2008 ; National Collaborating Centre for Acute Care [NICE] 2006 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The standards defined nutritional care by identifying the following processes. First, all patients are screened by the nursing staff using the Malnutrition Screening Tool, and those at risk are referred to the dietitian for further assessment and the development of a nutritional care plan in consultation with nurses . Nutritional screening by nursing staff is a requirement under Australian hospital standards .…”
Section: Introductionmentioning
confidence: 99%
“…First, all patients are screened by the nursing staff using the Malnutrition Screening Tool, and those at risk are referred to the dietitian for further assessment and the development of a nutritional care plan in consultation with nurses. [19][20][21][22][23] Nutritional screening by nursing staff is a requirement under Australian hospital standards. 24 Second, adequate staffing for mealtimes is ensured by nurses not taking breaks during this time and encouraging volunteers and family members to assist with this aspect of care.…”
Section: Introductionmentioning
confidence: 99%